CULTURE, HISTORY AND TRAUMATIC MEMORY: AN INTERPRETATION - Allan Young (Acta Bioethica, 2016)
Efforts to investigate psychiatric disorders across cultures routinely ignore a pervasive cultural influence, namely the culture of psychiatry . This article focuses on how the culture of psychiatry affects our understanding of posttraumatic stress disorder (PTSD). PTSD is diagnosed by means of standardized symptom criteria and scales. Yet it is a heterogeneous phenomenon. The illusion of homogeneity is fostered by a categorical conception of traumatic memory that homogenizes posttraumatic memories and erects an obstacle to investigating the disorder’s historical nature, clinical phenomenology, and neuro-physiology and neuro-anatomy. I illustrate this process, via an epidemic of PTSD that now affects a quarter of a million American war veterans.